Chan pin ling dao li jie chu chan pin jing li ru he da zao zhuo yue chan pin he tuan dui / = Product leadership : - Banfield, Richard; Eriksson, Martin; Walkingshaw, Nate (Ren min you dian chu ban she = Posts & Telecom Press, 2022)
Detailed summary in vernacular field only.